Gendered Violence, Intersectionalities and Resisting Gender Neutrality - Stubbs, Julie (Oñati Socio-Legal Series, 2015)
Developments in feminist theory and research towards a more complex approach to gender relations and a more differentiated understanding of gendered violence have been positive but also have been the subject of significant debate. Some debates have long histories, while others mark more newly emergent concerns. In this paper I reflect on three areas of debate: intersectionality, complex gendering and complex inequalities; differentiating between forms of gendered violence (with a focus on intimate partner violence (IPV)), and criminalisation. In each of these areas, feminist frameworks and knowledge concerning gendered violence have been challenged and the resurgence of gender neutral accounts has been notable. I argue that keeping a structural analysis to the fore provides the best way forward for constructive debate in the field aligned with feminist aspirations for the achievement of substantive equality.